The Dynamic Role of Moslem in Building Indonesia as a Nation-State - Ricardi S. Adnan (Indonesian Journal of Religion and Society, 2023)
This study figures out the historical journey of the Indonesian nation which is full of its own dynamics is marked by the prominent role of Moslem figures in fighting for and maintaining national unity. The socio-cultural diversity is vital capital as well as a big challenge for Indonesia in building a nation-state. For more than seventy years this pluralistic society has been united by one state ideology, namely "Pancasila" which is expressly stated in the constitution. Optimism was reflected in the economic progress achieved in the mid-1990s, but after the 1997-1998 economic crisis which was followed by a multidimensional crisis, social integration experienced major problems. This article explains the role of the Moslem community in establishing the Indonesian nation, seizing, and maintaining independence, as well as the potential threats to national integration. This article emphasizes again that the long journey of the Indonesian nation and the role of the Islamic community in its long history is an important capital that should not be forgotten in efforts to increase Indonesia's glory for the future. From independence until two-thirds of the century of it, the representation of Islamic groups is very calculated in managing government, however, in elections, they only have a significant enough vote but have never won. With a historical approach through a literature review, the author argues that there are many things that need to be done by the Indonesian people, especially the Moslem community to build Indonesia as a strong nation-state.